2021
DOI: 10.3390/ijms22168844
|View full text |Cite
|
Sign up to set email alerts
|

Ganglioside Composition Distinguishes Anaplastic Ganglioglioma Tumor Tissue from Peritumoral Brain Tissue: Complementary Mass Spectrometry and Thin-Layer Chromatography Evidence

Abstract: Gangliosides serve as antitumor therapy targets and aberrations in their composition strongly correlate with tumor growth and invasiveness. Anaplastic ganglioglioma is a rare, poorly characterized, malignant neuronal–glial tumor type. We present the first comparative characterization of ganglioside composition in anaplastic ganglioglioma vs. peritumoral and healthy brain tissues by combining mass spectrometry and thin-layer chromatography. Anaplastic ganglioglioma ganglioside composition was highly distinguish… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 61 publications
0
2
0
Order By: Relevance
“…In a sample from a human patient with GBM, GD3 and GT1 each accounted for 36% of the ganglioside content [101]. The ceramide composition of gangliosides from both types of tumors exhibited heterogeneity, with the fatty acid C24:1 found in GD3 and GT1 in GBM and C24:0 most abundant in GD3 from anaplastic ganglioglioma tissue [158]. Interestingly, using performance ion mobility separation mass spectrometry, Sarbu et al [101] identified 160 distinct components with high variability found in both the carbohydrate and ceramide components, adding another possible degree of complexity to the identification of ganglioside function.…”
Section: Gangliosides and Angiogenesismentioning
confidence: 99%
See 2 more Smart Citations
“…In a sample from a human patient with GBM, GD3 and GT1 each accounted for 36% of the ganglioside content [101]. The ceramide composition of gangliosides from both types of tumors exhibited heterogeneity, with the fatty acid C24:1 found in GD3 and GT1 in GBM and C24:0 most abundant in GD3 from anaplastic ganglioglioma tissue [158]. Interestingly, using performance ion mobility separation mass spectrometry, Sarbu et al [101] identified 160 distinct components with high variability found in both the carbohydrate and ceramide components, adding another possible degree of complexity to the identification of ganglioside function.…”
Section: Gangliosides and Angiogenesismentioning
confidence: 99%
“…Observations that gangliosides could affect angiogenesis led to a number of studies, some of which were performed using animal models of malignant brain tumors [for a review, see [157]. Subsequently, results of analyses of the ganglioside composition of tissues from two different types of human brain tumors, glioblastoma multiforme (GBM) [101] and anaplastic ganglioglioma [158], showed that both had high proportions of GD3. More specifically, GD3 concentration was more than 50% in anaplastic gangliogliomas, while in peritumoral and healthy brain tissue, it was <10% [158].…”
Section: Gangliosides and Angiogenesismentioning
confidence: 99%
See 1 more Smart Citation
“…The most common sphingoid base found in human gangliosides is sphingosine ( Ando and Yu, 1984 ; Sarbu et al, 2021 ), but GD2 ceramide can also include eicosphingosine, sphinganine, or phytosphingosine ( Ando and Yu, 1984 ; Colsch et al, 2011 ; Merrill, 2011 ; Sibille et al, 2016 ). In addition, fatty acids can be unsaturated, saturated, oxygenated ( Ladisch et al, 1989 ), and of different lengths, ranging from C16 to C24 ( Ando and Yu, 1984 ; Sjoberg et al, 1992 ; Serb et al, 2009 ; Balis et al, 2020 ; Fabris et al, 2021 ). The functional consequences of the heterogeneities of the ceramide tail remain largely unknown.…”
Section: Biological Significance Of Gd2 Structural Diversitymentioning
confidence: 99%
“…An innovative approach combining mass spectrometry and thin-layer chromatography has been performed by Fabris D. et al to provide a comparative characterization of ganglioside composition in a neuronal–glial type of tumor (AGGL), vs. peritumoral (PT) and normal brain tissues (NB). AGGL ganglioside composition was found to be highly altered as compared to peritumoral PT and NB tissues, including changes in both carbohydrate and ceramide residues of ganglioside species [ 5 ]. The additional contribution of this study is the characterization of the ganglioside composition in valuable and rarely accessible peritumoral tissues, since the important biochemical changes that occur within this area are considered responsible for tumor cell infiltration into the surrounding NB, promoting tumor recurrence and drug resistance.…”
mentioning
confidence: 99%